A quantum algorithm for minimal spanning tree - Aghaei, Mohammad Reza Soltan; Ahmad Zukarnain, Zuriati; Mamat, Ali; Zainuddin, Hishamuddin (IEEE, 2008)
Quantum computing algorithms are considered for several problems in graph theory. Classical algorithms involve searching over some space for finding the minimal spanning tree problem in a graph. We modify classical Primpsilas algorithm and replace quantum search instead of classical search, of which it will lead to more efficient algorithm. Also we proposed the structure for non-classical algorithms and design the various phases of the probabilistic quantum-classical algorithm for classical and quantum parts. Finally, we represent the result of implementing and simulating Primpsilas algorithm in the probabilistic quantum-classical algorithm.